PERANAN BUDAYA ORGANISASI DALAM KINERJA KARYAWAN CV. BRATAS PRATAMA TUBAN - Persada, Sapta Martandiyana Surya; Almanshur, Fauzan (Jurnal Manajemen, 2022)
Human resources are one of the important resources in an organization. Organizational culture is the willingness, ability and willingness of a person to adapt his behavior to the organizational culture that has high relevance to his willingness, ability and willingness to increase work productivity. The first purpose of this study was to determine the factors behind the formation of organizational culture in supporting employee performance at CV Bratas Pratama.. The second Knowing the application of organizational culture in CV. Bratas Pratama in supporting the performance of its employees. This study uses a qualitative method, with data collection techniques through interviews, observation and information documentation techniques as many as 2 people consisting of 1 main director of CV Bratas Pratama and 1 technician supervision of CV Bratas Pratama. The results of the research related to the role of organizational culture in supporting employee performance indicate that the applied organizational culture has been able to support employee performance improvement from year to year. It can be proven that the role of organizational culture has been complied with by employees effectively and efficiently, and the innovations given by superiors to employees to achieve company goals together can be seen in the achievement of project completion that is always on time in accordance with the contract agreement stated.